Healing evaluation of medicinal plants front dermal damages in murine model: a comparative analysis (Research, Society and Development, 2020)
The skin is one of the most important organs of the human body, and this makes healing an event of fundamental importance. In this way, medicinal plants have gained ground in the management of lesions as they demonstrate excellent clinical results, bringing rapid and effective tissue repair and reducing complications. To evaluate the effect of topical treatment of two formulations containing the hydroalcoholic extract of Anacardium occidentale L. and of the fresh extract of Aloe Vera L. on the healing of excisional wounds in Swiss mice. The hydroalcoholic extract of the cashews of the purple cashew tree obtained through a dynamic maceration process for 10 days and the fresh extract of aloe vera were used. In the experiment 40 mice were used. To evaluate the healing activity, the mice were divided into four groups of ten animals each (n = 10): GCP- Positive Control Group using Fibrinase®, GCN- Negative Control Group using the base cream without extract, GT-Ao Treatment Group Anacardium occidentale L and GT-Av Aloe Vera L. treatment group. The GT-Ao presented a thick leukocyte fibrin crust during the treatment, without interfering in the scar repair. The GT-Av expressed better data, such as 100% of the group healed on the 14th day and better rates of contraction throughout the study. Both treatment groups did not present any events that would infer healing. The results demonstrate that the topical use of the aforementioned plants used in excisional wounds in mice presents promising results for wound healing.